Screening of Cytotoxic Activity of Soluble Pigment Biomolecules from Actinomycetes Isolated from Various Locations in South Sulawesi - Akhmad, Wahyuni; Hartono, Hartono; Hala, Yusminah; Aziz, Andi Asmawati; Abidin, Hamdayani Lance; Ali, Alimuddin (Jurnal Veteriner; Vol 26 No 2 (2025)DO - 10.19087/jveteriner.2025.26.2.163, 2025)
The diversity of colors in metabolites, particularly soluble pigments secreted by actinomycetes, has been minimally reported as cytotoxic metabolites. This study aims to screen the cytotoxic activity of secondary metabolites, especially soluble pigments produced by tropical actinomycetes. Actinomycetes metabolites were produced through batch fermentation using 100 mL of Starch Nitrate broth media in 500 mL Erlenmeyer flasks. The resulting ethyl acetate extracts were tested for cytotoxicity against the MCF-7 cell line. The characterization of isolates was based on colony morphology and spore chain analysis. The results of this study showed that the cytotoxic activity of secondary metabolites against cancer cells (specifically MCF-7) was as follows: 30.016 ?g/mL for isolate Py/kM (yellow pigment), 27.53 ?g/mL for isolate Ac-e/b (pink pigment), 35.559 ?g/mL for isolate SM-r/B (brown pigment), 33.636 ?g/mL for isolate Lc-r/F (purple pigment), and 30.986 ?g/mL for isolate Dis 014 (orange pigment).